The effect of spin coating rate on morphology and optical properties of cuprous oxide thin film prepared by sol-gel technique - Dewi Suriyani, Che Halin, Dr. (Australian Ceramic Society, 2014)
Link to publisher's homepage at http://www.austceram.com/